INFLUENCE OF PHYSICAL ACTIVITY ON QUALITY OF LIFE OF BREAST CANCER PATIENTS - Barra, Alexandre Almeida; Makluf, Ana Silvia Diniz; Figueiredo, Elyonara Mello; Pereira, Danielle Aparecida Gomes; Barros, Cristóvão Pinheiro (Mastology, 2021)
Introduction: Breast cancer is the most common neoplasm among women. As a consequence of the increased number of cancer diagnoses, and concomitant mortality reductions for most types of cancer many patients live with physical and psychosocial problems associated with the disease and its treatment that may compromise their quality of life (QoL). Exercise has been recommended as part of standard care for patients with cancer to help prevent and manage physical and psychosocial problems and improve QoL. Objectives: The objective of the current study was to compare the impact of physical activity practice in women with breast cancer, through indicators of quality of life. Methods:This is a randomized study with breast cancer patients in a large general hospital in southeastern Brazil. The questionnaires were applied regarding function and quality of life (EORTC QLQ-C30 and BR-23). Patients were randomly allocated into two groups: control, without intervention and treatment group, with the practice of physical exercises and nutritional orientation. Physical activity was performed for three hours/week through active-assisted exercises of flexion, abduction, extension, and rotation of upper limbs and treadmill walking at a speed tolerated by the patient. After six months of participation, all patients were reassessed, with blindness of the investigator. Results: The study did not reveal statistical difference in the constructs cited (p>0.05) between the control group and the treatment group regarding “Global Health Status” “Functional Scale” and “Scale of Symptoms “, however the patients in physical activity presented better mood and confidence being more adapted to face the challenge of the disease. Conclusions: The practice of physical activity showed no benefit in improving quality of life and functional capacity in patients with breast cancer in the evaluation by questionnaires in a short period established, however, showed favorable trends for improvement in successive evaluations.